An unobtrusive swimming monitoring system for recreational and elite performance monitoring - James, D. A.; Burkett, B.; Thiel, D. V. (Procedia Engineering, 2011)
Swimming is one of Australia's most successful sports at international competition. This success is due to the elite level support provided at Australia's sports academies and institutes, together with strong recreational and developmental programmes. In recent years Australia's approach to elite level sport has been somewhat eroded as other countries adopt our processes, coupled with a shrinking talent pool nationally. Since early 2000 a technology initiative has been undertaken to help address this by offering a way to provide elite level support at the local level. Swimming assessment is traditionally a labour intensive process where stroke phase, stroke rates, stroke counts, and lap times are often manually recorded or extracted from video data. This manual process is dependent on high staffing levels and is generally unavailable for routine training activities or remote areas. Beyond the basic measures above the coordination of key body segments in swimming is of growing interest for swimmers and coaches though it is difficult to obtain. Understanding these movements can identify whether the action is enhancing swimming performance, or potentially harmful. The use of wearable sensors, and in particular inertial sensors, is an emerging field in sports monitoring and a promising tool for swimming assessment. This paper describes the scaling of wearable sensor technology from single device/single user to multiple devices/ multiple users together with a framework that allows near real time data analysis as well as post session and multi session. Results demonstrate the usefulness and feasibility for such devices in the preparation of athletes. The developed system demonstrates how analysis will facilitate the primary goals of developing athlete performance to be realised, both through poolside interventions and long term developmental planning.